2020
DOI: 10.1016/j.adro.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Polyethylene Glycol Hydrogel Spacer and Its Effect on Rectal Radiation Dose in Prostate Cancer Patients Receiving Proton Beam Radiation Therapy

Abstract: Purpose: To assess the efficacy of placing a polyethylene glycol (PEG) spacing hydrogel in patients undergoing proton beam radiation therapy for prostate cancer. This study also aims to assess the effect on rectal radiation dose of prostateerectum separation in various anatomic planes.Methods and Materials: Seventy-two consecutive prostate cancer patients undergoing conventionally fractionated pencil beam scanning proton radiation therapy with and without hydrogel placement were compared. Magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Furthermore, three other studies 24,25,27 also reported significant reductions in rectal dose volumes when comparing between the SpaceOAR and control groups; relative reductions were 37.5% in V70 (P < 0.01) for one study, 24 71.6% in V75 (P < 0.0001) for another study, 25 and 41.8% in V75 (P < 0.001) for the third study. 27 Three studies 16,18,22,24 showed SpaceOAR to not increase the radiation dose volume in neighbouring organs, particularly the bladder and penile bulb. The RCT 16 and a study by Whalley et al 22 reported no significant differences in dosimetry values (V40, V50, V70) for the bladder when comparing pre-SpaceOAR to post-SpaceOAR treatment plans.…”
Section: Prostate-rectum Separation and Dosimetry Profilementioning
confidence: 85%
See 4 more Smart Citations
“…Furthermore, three other studies 24,25,27 also reported significant reductions in rectal dose volumes when comparing between the SpaceOAR and control groups; relative reductions were 37.5% in V70 (P < 0.01) for one study, 24 71.6% in V75 (P < 0.0001) for another study, 25 and 41.8% in V75 (P < 0.001) for the third study. 27 Three studies 16,18,22,24 showed SpaceOAR to not increase the radiation dose volume in neighbouring organs, particularly the bladder and penile bulb. The RCT 16 and a study by Whalley et al 22 reported no significant differences in dosimetry values (V40, V50, V70) for the bladder when comparing pre-SpaceOAR to post-SpaceOAR treatment plans.…”
Section: Prostate-rectum Separation and Dosimetry Profilementioning
confidence: 85%
“…1). Of the 13 articles, five were of the same RCT, [16][17][18][19][20] two were prospective studies, 21,22 five were retrospective studies [23][24][25][26][27] in which two were of the same study, 25,26 and one was a pooled analysis 28 of the RCT 18 and a retrospective study. 24 Characteristics of the included articles are outlined in Table 2.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations